Supporting and Educating Traumatized Students : a Guide for School-Based Professionals. - Rossen, Eric Ph. D. (Oxford University Press, 2012)
Combining knowledge of the cognitive and behavioral effects of trauma, evidence-based interventions, educational best practices, and the experiences of veteran educators, Supporting and Educating Traumatized Students: A Guide for School-Based Professionals presents a new framework for assisting students with a history of trauma.